2011
DOI: 10.1002/ijc.26500
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and survival of head and neck cancer by HPV status: a cancer registry‐based study

Abstract: Elucidation of the role of human papillomavirus (HPV) in the etiology and prognosis of squamous carcinomas of the head and neck (HNSCC) is essential to optimize prevention and treatment strategies for this disease. We analyzed 385 HNSCC tissue blocks identified through a population-based cancer registry in Metropolitan Detroit for HPV DNA using a broad-spectrum PCR technique (SPF10-LiPA25) to correlate with patient and tumor characteristics and overall survival. Overall, HPV DNA (any type) was detected in 29.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
7
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 34 publications
6
85
7
5
Order By: Relevance
“…Rates of HPV positivity in the literature vary depending on the detection method used and the tissue types tested. Our rate of HR HPV positivity does not appear to differ significantly from a 2012 cancer registry study by Sethi et al [20] which had a prevalence of 29.4 % HPV positivity for carcinomas at all head and neck sites and reported a 50.6 % prevalence within carcinomas of the oropharynx. In the same study by Sethi et al [20] it was confirmed that HPV positivity (in large part HPV16), was associated with improved survival and that the survival advantage of HPV-positivity was limited to oropharyngeal sites.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Rates of HPV positivity in the literature vary depending on the detection method used and the tissue types tested. Our rate of HR HPV positivity does not appear to differ significantly from a 2012 cancer registry study by Sethi et al [20] which had a prevalence of 29.4 % HPV positivity for carcinomas at all head and neck sites and reported a 50.6 % prevalence within carcinomas of the oropharynx. In the same study by Sethi et al [20] it was confirmed that HPV positivity (in large part HPV16), was associated with improved survival and that the survival advantage of HPV-positivity was limited to oropharyngeal sites.…”
Section: Resultscontrasting
confidence: 65%
“…Our rate of HR HPV positivity does not appear to differ significantly from a 2012 cancer registry study by Sethi et al [20] which had a prevalence of 29.4 % HPV positivity for carcinomas at all head and neck sites and reported a 50.6 % prevalence within carcinomas of the oropharynx. In the same study by Sethi et al [20] it was confirmed that HPV positivity (in large part HPV16), was associated with improved survival and that the survival advantage of HPV-positivity was limited to oropharyngeal sites. Thus, in the absence of evidence for a prognostic role of HPV testing outside of the oropharynx and metastatic neck lymph nodes, these locations may not need HPV-ISH testing unless histologic and/or clinical features otherwise suggest HPV related cancers [21,22].…”
Section: Resultscontrasting
confidence: 65%
“…In another study of 57 oropharyngeal cancers, improved prognosis was observed among p16 positive versus negative cases initially treated with either radiotherapy or chemoradiotherapy (log-rank test p = 0.10) or by surgery with or without adjuvant radiotherapy (p = 0.07) [44]. A recent study similarly found improved overall survival in HPV-positive as compared to HPV-negative oropharyngeal cancers treated with radiotherapy, but found no improvement among those receiving no radiotherapy [45]. While estimates did not reach statistical significance, likely due to small numbers, our results showed an improvement in overall survival comparing HPV16 positive with HPV16 negative oropharyngeal cancers, irrespective of initial therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have noted that younger patients with H&N cancer squamous cell carcinoma (HNSCC) and minimal to no smoking history are more likely to have HPV-positive tumors compared to older patients. [23][24][25] Furthermore, patients with HPV-positive HNSCC generally tend to have better prognosis compared to their HPV-negative counterparts. [26][27][28] In this study, patients in the oral cavity and hypopharynx groups had low primary tumor volume reduction, which fits into the general response pattern for these subsites.…”
Section: Discussionmentioning
confidence: 99%